The New Markets Tax Credit and the Low-Income Housing Tax Credit: Can They Be Joined Efficiently?. - Martinez, Maritza. (2017)
Abstract: The purpose of this thesis is to understand whether two widely used tax credit programs, the New Markets Tax Credit and the Low-Income Housing Tax Credit, should be combined to create mixed-use, mixed income housing developments. The hypothesis for this research is that combining the tax credit programs under one ownership entity would allow for greater efficiencies in financing and in the development of mixed-use affordable housing projects. In order to answer this question several interviews were conducted with professionals in the fields of community economic development and affordable housing and two case study developments were researched. Recommendations address the need for the New Markets Tax Credit to be simplified and made permanent.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Rachel Bratt.; Committee: James Jennings.; Keyword: Urban planning.